A look to Peru through lived experience. An interview to Federico Prieto Celi - Dextre Coello, Tatiana (Mercurio Peruano, 2018)
Federico Prieto Celi, journalist, canonist, essayist and university professor, is one of those valuable Peruvians who participate in this valuable editorial initiative. He met the publication Mercurio Peruano when he was studying literature at the Catholic University, and it was directed by Víctor Andrés Belaunde.